The AT-hook DNA binding ability of the Epstein Barr Virus EBNA1 protein is necessary for the maintenance of viral genomes in latently infected cells - Chakravorty, Adityarup (Virology, 2015)
Epstein Barr Virus (EBV) is a human tumor virus that is causally linked to malignancies such as Burkitt’s lymphoma, and gastric and nasopharyngeal carcinomas. Tethering of EBV genomes to cellular chromosomes is required for the synthesis and persistence of viral plasmids in tumor cells. However, it is not established how EBV genomes are tethered to cellular chromosomes. We test the hypothesis that the viral protein EBNA1 tethers EBV genomes to chromosomes specifically through its N-terminal AT-hook DNA-binding domains by using a small molecule, netropsin, that has been shown to inhibit the AT-hook DNA-binding of EBNA1 in vitro. We show that netropsin forces the loss of EBV genomes from epithelial and lymphoid cells in an AT-hook dependent manner and that EBV-positive lymphoma cells are significantly more inhibited in their growth by netropsin than are corresponding EBV-negative cells.